Las «pasiones cognoscitivas» o la dimensión rebelde del conocer en régimen de pasión - Jacques Roux; Florian Charvolin; Aurélie Dumain (Revue d'anthropologie des connaissances)
The article argues that the notion of “cognitive passions”, through its multiple semantics, is heuristically powerful. It carries a tension of an enrolment of knowledge by an irresistible force that takes with it all possibility of reasoning; cognition, on the contrary, supposes a form of "relaxation" in the knowing posture. The article shows the potential radicality of the notion by confronting it with different field surveys. The aim is to reintroduce the taboo of passion into the study of knowledge in the making, with its cognitive and affective trials, voluntary commitment and attachment to the object under study, and participation in communities of enthusiasts or counter-passionates, the articulation of the subjects of passion and the subjects of knowledge, the derivation of the attributes of knowledge from passion, the epistemology of a "knowing with and in situation" and not only "on and at a distance", the question of great amateurs and that of the production of knowledge in public passions.